Heavy metal and PCB spatial distribution pattern in sediments within an urban catchment—contribution of historical pollution sources - Dias-Ferreira, Celia; Pato, Rosinda L.; Varejão, Jorge B.; Tavares, Alexandre O.; Ferreira, Antonio J. D. (Journal of soils and sediments, 2016)
Purpose This work analyzes polychlorinated biphenyl (PCB) and heavy metal contamination in fluvial sediments and soils in an urban catchment, according to the geo-accumulation index and to soil and sediment quality guidelines. The catchment is located in Coimbra, Portugal, being affected by frequent flooding, and its main stream is a tributary to one of the major rivers in Portugal (Mondego). Given the presence of industrial activities over time, some inputs of pollutants are expected, but so far, the legacy of historic pollution in this catchment has not yet been investigated. Materials and methods Twenty-five samples were collected from nine sampling sites at the depths of 0–20, 20–40 and 40–60 cm (to provide a historic perspective) along longitudinal profiles (streamlines) and in soils downstream of pollution sources. These samples were analyzed for six heavy metals (Cu, Cr, Pb, Cd, Zn, Ni), organic carbon, pH and ten PCBs (IUPAC numbers 28, 30, 52, 101, 138, 153, 166, 180, 204, 209). Results and discussion Total PCB concentrations ranged 0.47–5.3 ng g −1 dry weight (dw), and levels increase from the bottom to the top layers, suggesting an increased input over the last 100 years. PCB congener distribution shows the dominance of hexachlorobiphenyls, especially PCB138, suggesting the existence of local sources. PCB levels did not exceed sediment quality levels, placing sediments/soil under class 1 (not contaminated) or class 2 (trace contamination) with respect to PCB. All six metals exceeded the lowest effect level for sediment quality criteria, and three (Cd, Pb and Zn) largely exceeded the clean levels for dredged materials, placing sediments in class 5 (heavily contaminated). Sampling site S1 presented the highest concentrations of Zn, Pb and Cd, and historic vehicle traffic was identified as the most likely source, given the vertical and horizontal profiles. Conclusions High levels of Pb, Cd and Zn were found in fluvial sediments at some locations of the Loreto catchment, likely from historic traffic sources. This urban area is frequently affected by flooding events and is currently being subject to urban redevelopment. During these events/actions, historic pollutants in the sediments might surface and be redistributed, impacting the downstream ecosystem of the major Mondego River or increasing the risk of exposure of the urban population.